Comprehensive neurosurgery board review - Citow, Jonathan Stuart; Macdonald, R. Loch (Robert Loch); Refai, Daniel (Thieme, 2010)
Contains the information you need to prepare for the American Board of Neurological Surgery (ABNS) written examination. This title provides coverage of core concepts in anatomy, physiology, pathology, radiology, neurology, neurosurgery, and critical care. It is intended for neurosurgical residents preparing for the ABNS certification exam.